DOI: 10.22215/etd/2014-10292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Dual Tank Indirect Solar-Assisted Heat Pump System for a High Performance House

Abstract: This work focused on the design and evaluation of an integrated mechanical system, which incorporated a dual tank indirect solar-assisted heat pump, that offsets spaceheating, cooling, and domestic hot water loads for a high performance house. A model of the system was developed to investigate the effects of various parameters on the performance of the system. These parameters included the tank configurations, the solar collector size and orientation, and heat pump size and controls. In addition, an experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…Chu conducted a sensitivity analysis with the TRNSYS model, and found the optimal values for the construction of the experimental apparatus through a sensitivity analysis of the free energy fraction. In this case, a free energy fraction, or portion of energy that is collected from the sun and not supplied by utilities, of over 50% could be obtained [25]. Both studies found that sizing the heat pump correctly was the most sensitive factors on economics and total energy consumption.…”
Section: Solar Thermal Technology Is Popular In Areas With High Insolmentioning
confidence: 94%
See 2 more Smart Citations
“…Chu conducted a sensitivity analysis with the TRNSYS model, and found the optimal values for the construction of the experimental apparatus through a sensitivity analysis of the free energy fraction. In this case, a free energy fraction, or portion of energy that is collected from the sun and not supplied by utilities, of over 50% could be obtained [25]. Both studies found that sizing the heat pump correctly was the most sensitive factors on economics and total energy consumption.…”
Section: Solar Thermal Technology Is Popular In Areas With High Insolmentioning
confidence: 94%
“…Chu designed and tested a solar assisted heat pump system to highlight the sensitivity of many advanced heat pump system parameters such as COP, flow rate, and heat pump capacity to system design parameters [25]. The importance of efficient thermal stratification was also noted.…”
Section: Heat Pumpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the direct configuration, the solar collectors are integrated into the ASHP on the evaporator side, and the fluid circulating in the solar collector also serves as a refrigerant of the heat pump. Although direct systems demonstrate promising performance results, they are typically installed in climates milder than those of Canada (Chu, 2014). Contrarily, an indirect configuration is suitable for cold climates because the solar collector and heat pump form separate loops with an antifreeze solution and refrigerant, respectively.…”
Section: Bivalent Heat Pump Systemsmentioning
confidence: 99%
“…As part of her study on solar-assisted heat pump system, Chu (2014) provided an extensive survey of different system configurations with integrated diurnal TES used for space-heating and domestic hot water supply in residential applications. It was highlighted that the system proposed in the thesis was unique for satisfying both the heating and cooling demand of a residential house with consideration of the Canadian climate.…”
Section: Seasonal and Diurnal Applicationsmentioning
confidence: 99%